No causal relationship between ankylosing spondylitis and Parkinson's disease: Insights from Mendelian randomization studies - Jinhua Chen; Qiuhan Xu; Yiling Wang; Sisi Jiang; Baorong Zhang; Jun Tian (Heliyon)
Background: Retrospective cohort and cross-sectional studies have indicated an association between ankylosing spondylitis (AS) and Parkinson's disease (PD). However, owing the multitude of limitations, a consistent conclusion has not been determined. Furthermore, whether a causal relationship exists between these two diseases remains unclear. Methods: We conducted a two-way Mendelian randomization (MR) analysis using genome-wide association study data. For patients with PD, we utilised data from the ieu-b-7 database, whereas for patients with AS, we employed the three databases with the largest sample sizes for a combined analysis. These databases included ebi-a-GCST005529, finn-b-M13 ANKYLOSPON, and finn-b-M13 ANKYLOSPON STRICT. Our primary method of analysis was inverse variance weighting (IVW), supplemented by four other effective methods, to comprehensively infer a potential causal relationship between AS and PD. Additionally, we conduct various sensitivity analyses to assess the robustness of our estimates. Results: Based on our IVW MR analysis, no significant causal relationship between AS and PD was observed (odds ratio [OR] = 1.01, 95 % confidence interval [CI] = 0.99–1.03, P = 0.26). Additionally, our reverse MR analysis found no evidence supporting a significant causal relationship between PD and AS (OR = 0.93, 95 % CI = 0.85–1.01, P = 0.068). These results were substantiated by comprehensive sensitivity analyses that indicated minimal bias in the causal estimates. Conclusion: In contrast to numerous existing clinical studies, this study failed to provide evidence supporting a significant impact of AS on PD risk, or vice versa. Further investigations regarding the potential causal mechanisms linking AS and PD are warranted.